The Chaitén rhyolite lava dome: Eruption sequence, lava dome volumes, rapid effusion rates and source of the rhyolite magma - John Stith Pallister; Angela K. Diefenbach; William C. Burton; Jorge Muñoz; Julia P. Griswold; Luis E. Lara; Jacob B. Lowenstern; Carolina E. Valenzuela (Andean Geology, 2013)
We use geologic field mapping and sampling, photogrammetric analysis of oblique aerial photographs, and digital elevation models to document the 2008-2009 eruptive sequence at Chaitén Volcano and to estimate volumes and effusion rates for the lava dome. We also present geochemical and petrologic data that contribute to understanding the source of the rhyolite and its unusually rapid effusion rates. The eruption consisted of five major phases: 1. An explosive phase (1-11 May 2008); 2. A transitional phase (11-31 May 2008) in which low-altitude tephra columns and simultaneous lava extrusion took place; 3. An exogenous lava flow phase (June-September 2008); 4. A spine extrusion and endogenous growth phase (October 2008-February 2009); and 5. A mainly endogenous growth phase that began after the collapse of a prominent Peléean spine on 19 February 2009 and continued until the end of the eruption (late 2009 or possibly earliest 2010). The 2008-2009 rhyolite lava dome has a total volume of approximately 0.8 km3. The effusion rate averaged 66 m3s-1 during the first two weeks and averaged 45 m3s-1 for the first four months of the eruption, during which 0.5 km3 of rhyolite lava was erupted. These are among the highest rates measured world-wide for historical eruptions of silicic lava. Chaitén’s 2008-2009 lava is phenocryst-poor obsidian and microcrystalline rhyolite with 75.3±0.3% SiO2. The lava was erupted at relatively high temperature and is remarkably similar in composition and petrography to Chaitén’s pre-historic rhyolite. The rhyolite’s normative composition plots close to that of low pressure (100-200 MPa) minimum melts in the granite system, consistent with estimates of approximately 5 to 10 km source depths based on phase equilibria and geodetic studies. Calcic plagioclase, magnesian orthopyroxene and aluminous amphibole among the sparse phenocrysts suggest derivation of the rhyolite by melt extraction from a more mafic magmatic mush. High temperature and relatively low viscosity enabled rapid magma ascent and high effusion rates during the dome-forming phases of the 2008-2009 eruption.